(untitled) (Journal of Universal Science Research, 2024)
In this scientific article, correction of the shortcomings in the reading skills of students, development of reading skills, looking at the example of the English language developed. In addition, the methods of developing the reading competence of students of chemical and technological specialties in foreign language learning are analyzed.